Design of flameproof and waterproof natural textile fabrics - Abdullah, Turdimuhammad; Babayiğit, Levent; Turanlı, Aleyna; Turan, Recep Furkan; Dızman, Cemil (İdris Karagöz, 2025)
Natural fabrics, particularly linen and cotton are widely used in the textile industry due to their desirable properties, including breathability, durability, and comfort. However, their hydrophilic nature and inherent flammability pose limitations on their applications in various areas, such as residential settings, automotive vehicles, offices, and protective clothing. In these contexts, flame-retardant and hydrophobic properties are of crucial importance. To address this issue, we have applied UV-curable coatings on the surface of linen and cotton fabrics by employing two distinct acrylic polymer synthesis strategies. In the first approach, a methacrylated phenolic lipid was combined with n-alkyl methacrylate and copolymerized under UV exposure resulting in a hydrophobic and flame-retardant surface. In the second approach, 3-Aminopropyltriethoxysilane is coated on the natural fabric, and then 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) is applied above the 3-Aminopropyltriethoxysilane (APTES) surface prior to UV curing. A comprehensive study was conducted to evaluate the wetting behavior and flame retardancy of the fabric both before and after coating. This was done by employing water contact angle and limiting oxygen index testing. The findings of this study demonstrate that the hydrophobicity and flame retardancy of the fabric can be substantially enhanced through UV coating. Furthermore, the initial ratio between the applied monomers can be adjusted to fine-tune these properties. It is noteworthy that all the chemicals utilized in these investigations are derived from renewable bioresources, thereby ensuring sustainability and biocompatibility. This aspect holds significant importance for the textile industry, aligning with the growing demand for environmentally friendly and socially responsible manufacturing practices.

Dünyada en çok kullanılan doğal elyaf olarak bilinen doğal kumaş, tekstil sektörünün vazgeçilmez bir malzemesi haline geldi. Ancak bu malzemenin hidrofilik doğası ve doğal yanıcılığı, evler, otomotiv araçları, ofisler ve koruyucu giysiler de dahil olmak üzere çeşitli sektörlerdeki uygulamalarında sınırlamalar oluşturmaktadır. Bu bağlamlarda alev geciktirici ve hidrofobik özellikler hayati öneme sahiptir. Bu sorunu çözmek için iki farklı akrilik polimer sentez stratejisi kullanarak doğal kumaşa UV ile kürlenebilen kaplamalar uyguladık. İlk yaklaşımda, metakrilatlanmış bir fenolik lipit, n-alkil metakrilat ile birleştirildi ve UV'ye maruz bırakılarak kopolimerize edilerek hidrofobik ve alev geciktirici bir yüzey elde edildi. İkinci yaklaşımda, doğal kumaş üzerine 3-Aminopropiltrietoksisilan kaplandı ve ardından 9,10-dihidro-9-oksa-10-fosfafenantren-10-oksit (DOPO), 3-Aminopropiltrietoksisilan (APTES) yüzeyinin üzerine uygulanmadan önce uygulanır. UV kürleme sonrasında kumaşın hem kaplama öncesi hem de kaplama sonrası ıslanma davranışı ve alev geciktiriciliğini değerlendirmek için kapsamlı bir çalışma yapıldı. Bu, su temas açısı ve Sınırlayıcı Oksijen İndeksi Testi kullanılarak yapıldı. Bu çalışmanın bulguları, kumaşın hidrofobikliğinin ve alev geciktiriciliğinin UV kaplama yoluyla önemli ölçüde artırılabileceğini göstermektedir. Ayrıca uygulanan monomerler arasındaki başlangıç ??oranı, bu özelliklere ince ayar yapmak üzere ayarlanabilir. Bu araştırmalarda kullanılan tüm kimyasalların yenilenebilir biyolojik kaynaklardan elde edilmesi, dolayısıyla sürdürülebilirliğin ve biyouyumluluğun sağlanması dikkat çekicidir. Bu husus, çevre dostu ve sosyal açıdan sorumlu üretim uygulamalarına yönelik artan taleple uyumlu olarak tekstil endüstrisi için büyük önem taşımaktadır.
Aleve dayanıklı ve su geçirmez doğal tekstil kumaşların tasarımı
Keywords: Polymer Science and Technologies; Polimer Bilimi ve Teknolojileri [EN] Fabric Technologies; Kumaş Teknolojisi [EN] Textile Chemistry; Tekstil Kimyası